PENYULUHAN HUKUM PROSES PENYELESAIAN SENGKETA NON LITIGASI DI KELURAHAN NAMBO KECAMATAN NAMBO KOTA KENDARI - Taufiq Afoeli, La Ode Muhammad; Herman, Herman; Intan, Nur; Ukkas, Jumiati; Heryanti, Heryanti; Safiuddin, Sahrina; Tabiu, Ramadan (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2024)
The aim of holding this activity is to provide an enlightened understanding to the public regarding methodical variants in resolving legal disputes. This Community Service Activity is carried out through several stages which are described as follows: (1) Preparation Stage, including: Location survey, Stabilization and determination of location and targets , Preparation of materials/activity materials, (2) Implementation stage, carried out by: (a) Identification of legal problems to be able to find out the legal problems faced by partners, (b) Legal counseling or socialization is carried out in the form of interactive dialogue or question and answer first. preceded by a presentation or delivery of material from the resource person which is intended as an introduction to the discussion. The methods used during the process of community service activities include: (a) the lecture method chosen to provide direct explanations about the extension material, (b) the question and answer method which allows the community to gain as much knowledge as possible about the extension material. The results achieved in community service activities are socialization (legal counseling) regarding forms of dispute resolution in the community, especially using non-litigation methods. The public's interest in the material presented indicates that instruments to strengthen understanding of dispute resolution are really needed in people's daily lives. On the other hand, changes in societal paradigms in terms of dispute resolution will encourage the realization of complete legal order, both formal and material law so that a comprehensive legal development agenda can be realized.